PLANEACIÓN FINANCIERA EN LA FARMACIA “BOTICA COMUNITARIA” DE LA CIUDAD DE PIÑAS, PERÍODO 2021 - 2025 - Torres Torres., Erick Xavier (2021)
The thesis was carried out to meet the proposed general objective: "Carry out Financial Planning in the pharmacy" BOTICA COMUNITARIA ", of the city of Piñas, period 2021 - 2025", in order to implement the use of a financial tool in accordance with to the economic activities carried out daily by the pharmacy, this will make it possible to provide a significant contribution to the administrative staff and thus to the owner so that they can optimize the available resources and achieve increased profitability in the coming years and as a tool for decision-making financial In order to comply with the first and second specific objectives set out in the work, the current situation of the pharmacy was determined, showing that it does not carry out a financial diagnosis, in view of this, a current situational diagnosis was determined through the application of the companies' own indicators. As a result, the rotation of their inventories is good in 2019, with a rotation of approximately 5 times a year, on the other hand, the degree of indebtedness is high, reaching over 50%, which shows that the By having more debts, the pharmacy is exposed to a greater risk of not fulfilling its obligations. This is followed by a financial analysis report that includes a synthesis of the results obtained, conclusions and recommendations that serve as a guide for the owner to improve the performance of the company. For the third objective, the sales and purchase forecasts for the five years were prepared using an increase percentage of 9.84% obtained by applying the interest rate formula with historical data from the pharmacy, being so that for the year 2021 it was obtained sales of $ 1,738,468.72, for 2022 sales reach $ 1,909,534.04, in 2023 to $ 2,097,432.19, for the year 2024 a value of $ 2,303,819.52 is obtained and for the In the year 2025, sales will be $ 2,530,515.36, on the other hand, purchases in 2021 are $ 1,472,723.27, in 2022 your purchases will also increase to $ 1,693,632.47, by 2023 your purchases will be $ 1,947,677.34, in 2024 $ 2,239,828.95 and for the year 2025 a value of $ 2,575,803.29 was obtained, thus generating a database projected in the entry and exit programs of the cash, in addition the expenses were obtained by statistical data of the INEC and the Ministry of Labor; whereupon the cash budget was 5 prepared in order to anticipate the future availability of cash. To comply with the last objective set, the pro forma financial statements for the years 2021 to 2025 were developed to reflect the expected estimates of all assets, liabilities and results in order to provide a perspective of the future financial conditions that the company may have. pharmacy. Finally, the Balance Point of the financial projection was determined for the periods 2021, 2022, 2023, 2024 and 2025, it was carried out by classifying the fixed and variable costs of the operational activity, and thus establishing the amount of pharmaceutical product that It must be sold at a certain price to recover the money that was invested, without still receiving a profit.